P‐6.11: Research on the Influence of LCD dummy design on around mura. (4th October 2019) - Yu, Yun; Chen, Jing; Zhang, Pangling; Wang, Zui; Chen, Zhongtian; Yang, Yifeng; Zhao, Guo; Hsieh, Chung-Ching; Ray,
Abstract : The around Mura is a common defect of TFT_LCD. In this paper, the analysis of around Mura on the black and low gray level shows that the around display unevenness caused by the difference between the Transmittance and color coordinates of the Cell gap anomaly. Due to the poor design and process of the Dummy area, the AA edge glass Bending caused the unevenness of the around Cellgap. Through optimization of design and process, this paper effectively improves the issue; and gives the Dummy area related design optimization suggestions and process choices, which fundamentally solves around mura